DIE SCHILDFIBELN AUS DEM BEREICH DER DĘBCZYNO-GRUPPE - Riese, Torsten (Wydawnictwo Naukowe UAM, 2004)
Impressively decorated shield fibulae (Ger. Sehieldfibeln), used from phase C2 until phase C2/C3), belong to the most elaborated metal artifacts from the Late Roman Iron Age. They have been used by communities living in Scandinavia, on the Elbe lowlands as well as by society o f the Dębczyno group in Pomerania and the Cecele phase o f the Wielbark culture. The paper is an attempt o f a thorough chronological analysis o f these fibulae from the Dębczyno group along with the burial assemblages in which they had been found. It is suggested that these adornments were an element o f the women dress decoration as they have been found mostly in rich burials. It is argued that presence o f the shield fibulae on this territory is indicative o f wide contacts o f the Late Roman Iron Age elite with Scandinavia and the Elbe lowland region.
SHIELD FIBULAE FROM THE TERRITORY OF THE DĘBCZYNO GROUP